Secondary syphilis presenting as erythema multiforme in a HIV-positive homosexual man: a case report and literature review. (March 2019) - Liu, Hongfang; Goh, Beng-Tin; Huang, Taoyuan; Liu, Yinghui; Xue, Ruzeng; Ke, Wujian; Gu, Mei; Yang, Bin
Early syphilis can rarely cause erythema multiforme-type eruptions as well as triggering erythema multiforme (EM). EM-like lesions in secondary syphilis are characterized by clinical features of EM and laboratory tests consistent with secondary syphilis and the skin histology shows predominantly a plasma cell infiltrate with the presence of treponemes. When EM is triggered by early syphilis, the skin histology shows mixed inflammatory cells usually in the absence of treponemes in the skin lesion. There may also be mixed histology with the presence of treponemes in the absence of a plasma cell infiltrate and vice versa. We describe a case of secondary syphilis presenting as EM with bullae and histology showing EM features without a plasma cell infiltrate but positive for Treponema pallidum by immunohistochemical staining. The patient was also coinfected with cytomegalovirus, human immunodeficiency virus, and anal warts. The EM eruptions resolved with treatment for secondary syphilis with benzathine penicillin G.